2014
DOI: 10.1111/1471-0528.13119
|View full text |Cite
|
Sign up to set email alerts
|

Caesarean rates in Brazil: what is involved?

Abstract: Statistical data indicate that rates of caesarean births are increasing worldwide, 1 being particularly high in some countries, including Brazil; 2 however, consensus ends here. This is a controversial subject, particularly with regard to what would be the ideal caesarean rate and what are the determinants of high caesarean rates in some countries. Although factors that seem to contribute to a rise in caesarean rates all over the world are probably common to different countries, the reasons why countries with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0
4

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(31 citation statements)
references
References 8 publications
0
27
0
4
Order By: Relevance
“…In 2009, for the first time, the number of CSs exceeded the number of vaginal deliveries, reaching 57 % in 2014 [6]. This difference is significantly associated with the local coverage of private health insurance, because CS rates in private hospitals (80–90 %) are considerably higher than in the public sector (35–45 %) [710]. It is likely that many CS performed in Brazil are for non-medical reasons [1113].…”
Section: Introductionmentioning
confidence: 99%
“…In 2009, for the first time, the number of CSs exceeded the number of vaginal deliveries, reaching 57 % in 2014 [6]. This difference is significantly associated with the local coverage of private health insurance, because CS rates in private hospitals (80–90 %) are considerably higher than in the public sector (35–45 %) [710]. It is likely that many CS performed in Brazil are for non-medical reasons [1113].…”
Section: Introductionmentioning
confidence: 99%
“…According to the World Health Organization (WHO), cesarean rates have reached “epidemic proportions.” Cesarean rates have been reported at 36% in Korea and over 50% in China and Brazil . A recent study using survey data collected by the WHO concluded that, at the population level, rates higher than 10% are not associated with reductions in maternal or newborn mortality rates .…”
Section: Introductionmentioning
confidence: 99%
“…15 The association of higher PLCD rates with reduced rates of stillbirth and perinatal death was stronger in the least-developed countries yet persisted in high HDI-countries where overuse of CD has been reported. 20 21 23 35 We recently reported that the increase in CD rates observed between two WHO surveys (conducted in 2003-2005 and 2011-2012) 28 did not appear to contribute to improved neonatal outcomes observed in these countries. 36 Findings from these and our current study suggest that the increase in PLCD has occurred mostly where it is not needed, but that improved access to that invention among those in need could improve birth outcomes, although at the cost of higher preterm birth rates.…”
Section: Discussionmentioning
confidence: 96%
“…15 Even in countries such as Brazil 20 and China 21 where excessive CD is of concern, reports continue to show wide socioeconomic disparities in access to such interventions when required. 22 23 Compared with the vast literature on overall rates of CD and their potential maternal and neonatal consequences, we are aware of no previous study from low-income or middle-income countries assessing whether use of LI and/or PLCD are associated with improvement in perinatal survival and increased risk of late preterm birth.…”
Section: Bmj Global Healthmentioning
confidence: 99%